Pengembangan Buku Pedoman Permainan Tradisionalu untuk Menumbuhkan Karakter Toleransi Anak Usia 6-8 Tahun - Kania Dyah Ayu Kirana; Gregorius Ari Nugrahanta (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study was to develop a traditional game manual to improve the character of tolerance for children aged 6-8 years. This study was conducted with the ADDIE type of research and development (R & D) method. seven teachers from various regions for needs analysis, nine validators for expert judgements, and six children for a preliminary field testing participated in this study. The results showed 1) The traditional game manual was developed according to the stages of ADDIE type, namely Analyse, Design, Develop, Implement, and Evaluate; 2) The quality of the traditional game manual was in the “Very good” category equivalent to a score of 3,92 (Scale 1-4) with the recommendation “No need for revision”; and 3) The application of the manual effected on children’s tolerance character. The significance test showed (5) = 18,508; < 0,05. The effect size was = 0,99 which was included in the “big effect” category or equivalent to 98,57%. It meant that the implementation could explain 98,57% of variance changes in tolerance characters. The test for the effectiveness of the manual showed N-gain score of 94,498% equivalent to the “High” category. Keywords: traditional games, tolerance character, manual